School-Based Health Centers Addressing Health Equity for LGBTQ + Patients (SBHCs HELP): protocol for a stepped-wedge trial to implement innovations promoting structural competency - Cathleen E. Willging; Daniel Shattuck; Marisa Sklar; Rachel A. Sebastian; Robert L. Stout; Mary M. Ramos (BMC, 2024)
Abstract Background School-based health centers (SBHCs) provide vital behavioral, sexual, and reproductive healthcare services to school-aged youth across the United States. Adolescents who are sexual and gender diverse (SGD) are far more likely to suffer from adverse health outcomes than their cisgender and heterosexual peers. Emerging structural competency frameworks call for cultivating capacities in SBHCs to modify organizational service delivery environments, including provider and staff knowledge and behaviors, to influence SGD adolescent well-being. Nationally recognized guidelines for nurturing structural competency include (1) adopting, disseminating, and adhering to SGD supportive policies and procedures; (2) creating welcoming physical environments; (3) systematically documenting and using sexual orientation and gender identity information in clinical care; (4) training all employees in best practices for interacting with SGD patients; and (5) developing the clinical workforce to deliver high-quality services to SGD patients. This community-engaged study will test the effectiveness of the Dynamic Adaptation Process (DAP) in implementing these guidelines in SBHCs in culturally and geographically diverse areas of New Mexico. Methods We will conduct mixed-method readiness assessments to identify inner- and outer-context determinants affecting the implementation of structurally competent changes in SBHCs; employ a stepped-wedge trial to examine how the DAP-enabled implementation impacts adoption and changes in SBHC, student (patient), and implementation outcomes; and investigate inner- and outer-context determinants, bridging factors, and associated mediators and moderators influencing implementation processes and outcomes related to guideline adoption and SGD student care (e.g., reduced barriers, greater satisfaction and engagement). Discussion This study addresses the long-term goal of high-quality care and decreased health disparities for SGD youth. As investments in SBHCs rise nationwide, opportunities to enhance services for SGD youth will also grow. This study will demonstrate the usefulness of a multifaceted implementation strategy, the DAP, in helping SBHCs build structural competency to serve a sizeable population of students affected by stigmatization, discrimination, and other social forces that create inequities in health. Accordingly, we will advance a model featuring a set of implementation strategies to reduce knowledge and practice gaps, create welcoming environments, and improve the quality of care for SGD youth. Trial registration ISRCTN13844475; 20 September 2024.